A Supramolecular Approach to the Preparation of Nanographene Adlayers Using Water‐Soluble Molecular Capsules. Issue 47 (23rd October 2018) - Origuchi, Sakura; Kishimoto, Mai; Yoshizawa, Michito; Yoshimoto, Soichiro
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are excellent building blocks for the creation of two‐dimensional (2D) nanosheets. However, large PAHs tend to exhibit poor or no solubility in organic solvents and water. To overcome this issue, we employed water‐soluble micellar capsules consisting of V‐shaped amphiphilic molecules. Characteristic electrochemical behavior was observed in 0.1 m H2 SO4 in the presence of the water‐soluble capsules containing PAHs, such as ovalene, circobiphenyl, and dicoronylene. Furthermore, under these conditions, PAHs were released from the capsules, resulting in the formation of a 2D adlayer of PAHs at the electrochemical interface. Finally, using electrochemical scanning tunneling microscopy, we demonstrate that our molecular containers based on water‐soluble molecular capsules allow the facile preparation of 2D PAH adlayers in addition to structurally controlling nanostructure formation on Au surfaces. Abstract : Packaged and delivered : Water‐soluble molecular capsules consisting of V‐shaped amphiphiles were designed for the uptake of polycyclic aromatic hydrocarbons (PAHs). The PAHs were released from the molecular containers in 0.1 m H2 SO4 at an electrochemical interface, thus enabling the facile preparation of 2D PAH adlayers on an Au surface with controlled nanostructure formation (see picture).